Skin concerns in patients with trisomy 21 (Down syndrome): A Mayo Clinic 22‐year retrospective review. (18th August 2021) - Wentworth, Ashley B.; Hand, Jennifer L.; Davis, Dawn M.; Tollefson, Megha M.
Abstract: Background/Objectives: Trisomy 21 has known associated clinical phenotypes, including skin and soft tissue concerns. However, the overall prevalence and types of findings are largely unclear. Methods: A retrospective review of children with trisomy 21 and one or more dermatologic diagnoses, seen from 1/1/1994 to 7/1/2016, was performed to record dermatologic diagnoses. If one or more diagnoses were confirmed, further data were collected, including demographics, medical specialty, referrals to dermatology, treatment, complications, and follow‐up. Results: One hundred and seventy‐four patients with a diagnosis of trisomy 21 aged 18 years or younger were confirmed to have one or more dermatologic diagnoses. In a total of 479 dermatologic diagnoses, superficial mycoses (12%), skin and soft tissue infections (10%), dermatitis (8%), and folliculitis (8%) were most common. Diagnoses were most commonly made as an outpatient (91%) and by general pediatrics (45%) or dermatology (25%). A significant difference ( P < .05) in the frequency of various diagnoses made by different specialties was observed. A significant difference ( P < .05) in the treatments recommended by different specialties was also observed. Referrals to dermatology were infrequent (6%). However, a frequent change in diagnosis (61%) or treatment (68%) for patients referred to dermatology was observed. Conclusions: Children with trisomy 21 are most commonly diagnosed with superficial mycoses, skin and soft tissue infections, dermatitis, and folliculitis. The majority of diagnoses were made by general pediatricians and although dermatology referral was rarely necessary, consultations often resulted in change of diagnosis and/or treatment, supporting consideration of early and frequent dermatology referral.